Negative electrode material and preparation method and application thereof

By adopting a composite coating structure in the silicon-carbon negative electrode material and using conductive network and amorphous carbon to improve density and conductivity, the existing technology solves the problem of excessive production gas and electrochemical performance of negative electrode materials during battery use. Poor problem, achieving the effects of high energy density and cycle stability.

CN119361631APending Publication Date: 2025-01-24HUNAN SHINZOOM TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411444232.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing silicon-carbon anode materials will produce too much production gas during the use of the battery, and the carbonization temperature of the carbon coating will affect its electrochemical performance.

Method used

The composite overwrite structure is used, where the conductive network and the non -fixed carbon in the conductive network gap are jointly constructed, forming a conductive pathway between the silicon carbon core and the outside world, increasing density and reducing the surface area of ​​the ratio.

Benefits of technology

The electronic conductivity and rate performance of the negative electrode material are improved, ensuring high energy density and cycle stability, and extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361631A_ABST
    Figure CN119361631A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method and application thereof, the negative electrode material comprises a silicon-carbon inner core and a composite coating layer arranged on the surface of the silicon-carbon inner core, and the composite coating layer comprises a conductive network and amorphous carbon filled in gaps of the conductive network. The negative electrode material provided by the invention is good in conductivity and high in structural reliability, and is beneficial to improving the cycling stability and the rate capability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to negative electrode materials and preparation methods and applications thereof. Background Art

[0002] At present, silicon-carbon negative electrode materials have excellent cycle life and energy density, which can alleviate the volume expansion of silicon materials and improve the safety performance of batteries. Conventional methods deposit silicon in a porous carbon matrix, and the obtained negative electrode material has a large specific surface area, which increases the amount of binder and solvent used in electrode preparation, and the problem of excessive gas production will occur during the use of the battery. In the related art, carbon coating can be performed on silicon-carbon negative electrode materials to reduce the specific surface area, but too high a carbonization temperature will cause the silicon material to change and reduce the electrochemical properties of the negative electrode material. Too low a carbonization temperature will result in a low degree of carbonization of the carbon coating layer, poor electronic conductivity, and poor rate performance. Therefore, there is a need for a negative electrode material that has both high energy density, high rate performance and good cycle stability. Summary of the invention

[0003] In view of this, the present application provides a negative electrode material and a preparation method and application thereof. The composite coating layer of the negative electrode material includes a conductive network and amorphous carbon filled in the voids of the conductive network. The conductive network forms a conductive path between the silicon-carbon core and the outside world. The amorphous carbon filled in the voids of the conductive network can increase the density of the composite coating layer, which not only reduces the specific surface area of ​​the negative electrode material, but also increases the electronic conductivity of the negative electrode material, thereby ensuring high energy density and improving the electrochemical performance of the battery.

[0004] In a first aspect, the present application provides a negative electrode material, which includes a silicon-carbon core and a composite coating layer arranged on the surface of the silicon-carbon core, wherein the composite coating layer includes a conductive network and amorphous carbon filled in the gaps of the conductive network.

[0005] Optionally, the silicon-carbon core includes porous carbon and silicon nanoparticles filled in the pores of the porous carbon;

[0006] Optionally, the silicon nanoparticles include one or more of crystalline silicon and amorphous silicon.

[0007] Optionally, the conductive network is formed by a conductive agent.

[0008] Optionally, the conductive agent includes one or more of carbon nanotubes, conductive carbon black and nano silver wires.

[0009] Optionally, in the negative electrode material, the mass percentage of the composite coating layer is 0.01%-5%.

[0010] The negative electrode material provided in the present application has both low specific surface area and high energy density, thereby improving the safety performance and electrochemical performance of the battery.

[0011] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising:

[0012] The conductive agent, the binder and the silicon-carbon core are mixed, and a negative electrode material precursor binder is obtained after heat treatment; the negative electrode material precursor is mixed with a carbon source gas, and a negative electrode material is obtained after vapor deposition.

[0013] Optionally, the mass ratio of the silicon-carbon core, the binder and the conductive agent is 100:(0.1-1):(0.2-1).

[0014] Optionally, the temperature of the heat treatment is 500°C-550°C, and the time of the heat treatment is greater than or equal to 3 hours.

[0015] Optionally, the temperature of the vapor deposition is less than or equal to 600° C., and the time of the vapor deposition is 30 min-2 h.

[0016] Optionally, the carbon source gas includes one or more of alkanes, alkenes, alkynes and aromatic hydrocarbons.

[0017] Optionally, the binder includes one or more of acrylic acid, acrylic ester, terephthalate, polyacrylonitrile, glucose, maltose, polyacrylic acid, polymethyl methacrylate, phenolic resin and arabic resin.

[0018] The preparation method of the negative electrode material provided in the present application is novel, the preparation process is simple, and the prepared product has excellent performance.

[0019] In a third aspect, the present application provides a negative electrode plate, which includes a negative electrode collector and a negative electrode active material layer arranged on the surface of the negative electrode collector, and the negative electrode active material layer includes the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.

[0020] The negative electrode plate provided in the present application has good cycle stability and high energy density, which is beneficial to improving the safety performance of the battery.

[0021] In a fourth aspect, the present application provides a battery, comprising the negative electrode plate described in the third aspect.

[0022] The battery provided in this application has a long service life, high safety performance, and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0024] Figure 1 A schematic diagram of the cross-sectional structure of a negative electrode plate provided in one embodiment of the present application. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] The present application provides a negative electrode material, which includes a silicon-carbon core and a composite coating layer arranged on the surface of the silicon-carbon core, and the composite coating layer includes a conductive network and amorphous carbon filled in the gaps of the conductive network. In the present application, the silicon-carbon core can improve the energy density of the negative electrode material and increase the capacity of the battery; the composite coating layer can isolate the silicon-carbon core from the outside world, inhibit the volume expansion of the silicon material in the silicon-carbon core, and improve the cycle stability and structural reliability of the negative electrode material; in the coating layer, the conductive network and the amorphous carbon jointly construct a conductive path connecting the silicon-carbon core with the outside world, improve the electronic conductivity and first-cycle efficiency of the negative electrode material, and the amorphous carbon filled in the gaps of the conductive network can increase the density of the composite coating layer, reduce the specific surface area of ​​the negative electrode material, and improve the rate performance of the negative electrode material. The negative electrode material provided by the present application has good structural stability, high energy density, and good rate performance, which is conducive to extending the cycle life and electrochemical performance of the battery.

[0027] In one embodiment of the present application, in the negative electrode material, the mass percentage of the composite coating layer is 0.1%-5%, which can not only improve the structural stability of the negative electrode material, but also maintain the negative electrode material with a high energy density. Specifically, in the negative electrode material, the mass percentage of the composite coating layer can be but is not limited to 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, etc. In one embodiment of the present application, in the negative electrode material, the mass percentage of the composite coating layer can be 0.1%-2%. In another embodiment of the present application, in the negative electrode material, the mass percentage of the composite coating layer can be 1%-5%.

[0028] In one embodiment of the present application, the conductive agent forms a conductive network on the surface of the silicon-carbon core, which is conducive to the formation of a conductive path between the silicon-carbon core and the outside world, improves the conductivity of the negative electrode material, and enhances the electrochemical performance of the battery. Specifically, the conductive agent may include but is not limited to one or more of carbon nanotubes, conductive carbon black, and nano silver wires. In one embodiment of the present application, the conductive agent may be a carbon nanotube, which may be single-walled or multi-walled. In another embodiment of the present application, the conductive agent may be a nano silver wire.

[0029] In one embodiment of the present application, the silicon-carbon core includes porous carbon and silicon nanoparticles filled in the pores of the porous carbon, which is beneficial to improving the energy density and conductivity of the negative electrode material. Specifically, the silicon nanoparticles may include, but are not limited to, one or more of crystalline silicon and amorphous silicon. In one embodiment of the present application, the silicon nanoparticles may be crystalline silicon.

[0030] In one embodiment of the present application, the silicon-carbon kernel can improve the energy density of the negative electrode material, and the particle size D50 of the silicon-carbon kernel is 0.01μm-20μm. The appropriate silicon-carbon kernel particle size can improve the energy density and structural stability of the negative electrode material. Specifically, the particle size D50 of the silicon-carbon kernel can be, but is not limited to, 0.01μm, 1μm, 2μm, 5μm, 10μm, 15μm, 18μm or 20μm, etc. In one embodiment of the present application, the particle size D50 of the silicon-carbon kernel can be 0.01μm-10μm. In another embodiment of the present application, the particle size D50 of the silicon-carbon kernel can be 8μm-20μm.

[0031] In one embodiment of the present application, the mass percentage of silicon in the silicon-carbon core is 15%-85%. Specifically, the mass percentage of silicon in the silicon-carbon core can be, but is not limited to, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 85%. In one embodiment of the present application, the mass percentage of silicon in the silicon-carbon core can be 15%-65%. In another embodiment of the present application, the mass percentage of silicon in the silicon-carbon core is 55%-85%.

[0032] In one embodiment of the present application, the powder resistivity of the silicon carbon core is 0.1 Ω·cm-50 Ω·cm, and the specific surface area of ​​the silicon carbon core is 1 m 2 g -1 -100m 2 g -1 The appropriate powder resistivity and specific surface area of ​​the silicon carbon core can improve the electrochemical performance of the negative electrode material. Specifically, the powder resistivity of the silicon carbon core can be, but is not limited to, 0.1Ω·cm, 1Ω·cm, 5Ω·cm, 10Ω·cm, 20Ω·cm, 30Ω·cm, 40Ω·cm or 50Ω·cm, etc.; the specific surface area of ​​the silicon carbon core can be, but is not limited to, 1m 2 g -1 、10m 2 g -1 、20m 2 g -1 、40m 2 g -1 、60m 2 g -1 、80m 2 g -1or 100m 2 g -1 In one embodiment of the present application, the powder resistivity of the silicon carbon core can be 0.1Ω·cm-30Ω·cm, and the specific surface area of ​​the silicon carbon core can be 1m 2 g -1 -60m 2 g -1 In another embodiment of the present application, the powder resistivity of the silicon carbon core can be 25Ω·cm-50Ω·cm, and the specific surface area of ​​the silicon carbon core can be 50m 2 g -1 -100m 2 g -1 .

[0033] In one embodiment of the present application, the powder resistivity of the negative electrode material is less than or equal to 3Ω·cm. A suitable powder resistivity of the negative electrode material is beneficial to the conductivity of the negative electrode material, thereby improving the electrochemical performance of the battery. Specifically, the powder resistivity of the negative electrode material may be, but is not limited to, 0.1Ω·cm, 1Ω·cm, 1.5Ω·cm, 2Ω·cm, 2.5Ω·cm, 3Ω·cm, etc. In one embodiment of the present application, the powder resistivity of the negative electrode material is 0.5Ω·cm-2.5Ω·cm.

[0034] The present application also provides a method for preparing a negative electrode material, comprising:

[0035] S101: mixing the silicon-carbon core, the binder and the conductive agent, and performing heat treatment to obtain a negative electrode material precursor;

[0036] S102: Mix the negative electrode material precursor with the carbon source gas, and obtain the negative electrode material after vapor deposition. The preparation method provided by the present application is novel, the preparation process is simple, and the obtained negative electrode material has high structural stability and good conductivity, which is conducive to improving the energy density and rate performance of the negative electrode sheet, and improving the battery capacity and cycle life.

[0037] In one embodiment of the present application, the silicon carbon core, the conductive agent, the binder and the solvent are mixed to obtain a mixed solution, which is conducive to the dispersion of each component in the solution and improves its coating effect. The solvent can be but is not limited to N-methylpyrrolidone. In one embodiment of the present application, the mass percentage of the conductive agent in the conductive agent solution is 3%-5%.

[0038] In one embodiment of the present application, the mixing time is greater than or equal to 2 hours, which is conducive to the dispersion of the conductive agent on the surface of the silicon carbon core and the subsequent coating process. Specifically, the mixing time can be, but is not limited to, greater than or equal to 2 hours, greater than or equal to 2.5 hours, greater than or equal to 3 hours, greater than or equal to 3.5 hours, or greater than or equal to 4 hours. In one embodiment of the present application, the mixing time can be 3 hours. In another embodiment of the present application, the mixing time can be 5 hours.

[0039] In one embodiment of the present application, the temperature of the heat treatment is 500°C-550°C, and the time of the heat treatment is greater than or equal to 3h. The heat treatment can make the conductive agent form a conductive network on the surface of the silicon-carbon core, promote the combination of the silicon-carbon core and the conductive agent, and improve the structural stability of the negative electrode material. Specifically, the temperature of the heat treatment may be, but not limited to, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C, etc.; the time of the heat treatment may be, but not limited to, greater than or equal to 3h, greater than or equal to 3.5h, greater than or equal to 4h, greater than or equal to 4.5h or greater than or equal to 5h, etc. In one embodiment of the present application, the temperature of the heat treatment may be 500°C-530°C, and the time of the heat treatment may be greater than or equal to 4h. In another embodiment of the present application, the temperature of the heat treatment may be 520°C-550°C, and the time of the heat treatment may be greater than or equal to 4.5h.

[0040] In one embodiment of the present application, the binder in the coating layer can improve the combination of the conductive agent and the silicon-carbon core, and improve the structural reliability and electronic conductivity of the negative electrode material. Specifically, the binder can include, but is not limited to, one or more of acrylic acid, acrylate, terephthalate, polyacrylonitrile, glucose, maltose, polyacrylic acid, polymethyl methacrylate, phenolic resin and arabic resin. In one embodiment of the present application, the binder can be polyacrylonitrile. In another embodiment of the present application, the binder can be glucose. In some embodiments, the binder can be a small molecule that is easily soluble in an organic solvent or easily polymerized.

[0041] In the present application, the mass ratio of the silicon-carbon core, the binder and the conductive agent is 100: (0.1-1): (0.2-1). The appropriate mass ratio can improve the energy density and conductivity of the negative electrode material, have high structural stability, and improve the cycle stability of the battery. Specifically, the mass ratio of the silicon-carbon core, the binder and the conductive agent can be, but is not limited to, 100: 0.2: 0.4, 100: 0.3: 0.3, 100: 0.5: 0.5, 100: 0.6: 0.6, 100: 0.7: 0.6, 100: 0.8: 0.7, 100: 0.9: 0.9 or 100: 1: 1, etc. In one embodiment of the present application, the mass ratio of the silicon-carbon core, the binder and the conductive agent can be 100: (0.1-0.6): (0.2-0.7). In another embodiment of the present application, the mass ratio of the silicon-carbon core, the binder, and the conductive agent may be 100:(0.3-1):(0.5-1).

[0042] In this application, controlling the silicon-carbon core, binder and conductive agent within the above range will help improve the conductivity of the negative electrode material. If the binder is excessive, the binder will not be completely carbonized at a heat treatment temperature of 500°C-550°C, which will deteriorate the conductivity of the negative electrode material. If the amount of binder added is too little, it will be difficult to coat the conductive agent on the surface of the silicon-carbon material, and the fast charging performance will be difficult to effectively improve.

[0043] In one embodiment of the present application, mixing and heat treatment are performed in an inert environment, which is beneficial to prevent the negative electrode material from being contaminated.

[0044] In one embodiment of the present application, the negative electrode material precursor may also be prepared by a spray drying method, a volatile solvent method, etc., and the preparation needs to be performed in an oxygen-free and water-free environment.

[0045] In one embodiment of the present application, the carbon source gas can be carbon-coated on the surface of the negative electrode material precursor to form a coating layer to improve the structural stability and electrical conductivity of the negative electrode material. Specifically, the carbon source gas may include but is not limited to one or more of alkanes, alkenes, alkynes and aromatic hydrocarbons. In one embodiment of the present application, the carbon source gas may be an alkyne, such as acetylene. In another embodiment of the present application, the carbon source gas may be propyne. In some embodiments, the carbon source gas is a gas or organic matter that can undergo a carbonization reaction at 600°C.

[0046] In one embodiment of the present application, the temperature of the vapor deposition (CVD) is less than or equal to 600°C, and the time of the vapor deposition is 30min-2h. Suitable vapor deposition conditions can form a coating layer of suitable thickness on the surface of the core to avoid excessive vapor deposition leading to reduced conductivity of the negative electrode material. Specifically, the temperature of the vapor deposition may be, but is not limited to, less than or equal to 600°C, less than or equal to 580°C, less than or equal to 560°C, less than or equal to 550°C, less than or equal to 540°C or less than or equal to 500°C, etc.; the time of the vapor deposition may be, but is not limited to, 30min, 50min, 60min, 80min or 2h, etc. In one embodiment of the present application, the temperature of the vapor deposition may be 500°C-530°C, and the time of the vapor deposition may be 30min-80min. In another embodiment of the present application, the temperature of the vapor deposition may be 520°C-550°C, and the time of the vapor deposition may be 70min-120min. The specific vapor deposition time can be determined based on factors such as the specifications of the selected deposition equipment, the type of carbon source gas, the gas velocity, the specific cracking temperature, the specific surface area of ​​the silicon-carbon core used, the quality of the coating raw materials input, and the target coating thickness.

[0047] In one embodiment of the present application, a method for preparing a silicon-carbon core is also provided, comprising: mixing porous carbon and a silicon source gas, and obtaining the silicon-carbon core by a vapor deposition reaction.

[0048] In one embodiment of the present application, the particle size D00 of the porous carbon is greater than or equal to 1 μm, the particle size D50 of the porous carbon is 4 μm-20 μm, and the particle size D100 of the porous carbon is less than or equal to 60 μm. The porous carbon has a small particle size and a short overall pore path, which is conducive to the deposition of silicon inside the skeleton of the porous carbon and improves the dynamic properties of the silicon-carbon core.

[0049] In one embodiment of the present application, the tap density of the porous carbon is greater than or equal to 0.2 g / cm 3 The appropriate tap density can increase the tap density of the silicon-carbon core, which is beneficial to increase the compaction density of the negative electrode sheet and the energy density of the battery. Specifically, the tap density of the porous carbon can be, but is not limited to, greater than or equal to 0.2 g / cm 3 , greater than or equal to 0.3g / cm 3 , greater than or equal to 0.4g / cm 3 , greater than or equal to 0.5g / cm 3 Or greater than or equal to 0.6g / cm 3 In one embodiment of the present application, the tap density of the porous carbon can be 0.3 g / cm 3 In another embodiment of the present application, the tap density of the porous carbon can be 0.4 g / cm 3 .

[0050] In one embodiment of the present application, the total pore volume of the porous carbon is 0.1 g / cm 3 -2g / cm 3 The appropriate pore volume can increase the deposition amount of silicon source gas inside the porous carbon, which is beneficial to improve the energy density of the negative electrode material. Specifically, the total pore volume of the porous carbon can be, but is not limited to, 0.1 g / cm 3 , 0.5g / cm 3 , 0.8g / cm 3 , 1g / cm 3 , 1.2g / cm 3 , 1.5g / cm 3 , 1.8g / cm 3 or 2g / cm 3 In one embodiment of the present application, the total pore volume of the porous carbon can be 0.4 g / cm 3 -1.2g / cm 3 , which is beneficial to further improve the energy density of the negative electrode material. In another embodiment of the present application, the total pore volume of the porous carbon can be 1g / cm 3 -2g / cm 3 .

[0051] In one embodiment of the present application, the specific surface area of ​​the porous carbon is 500 m 2 / g-2000m 2 / g, a suitable specific surface area can increase the amount of silicon deposition and improve the energy density of the negative electrode material. Specifically, the specific surface area of ​​the porous carbon can be but is not limited to 500m 2 / g、600m 2 / g、800m 2 / g、1000m 2 / g、1500m 2 / g、1800m 2 / g or 2000m 2 In one embodiment of the present application, the specific surface area of ​​the porous carbon is 500 m 2 / g-1500m 2 In another embodiment of the present application, the specific surface area of ​​the porous carbon can be 1200 m 2 / g-2000m 2 / g.

[0052] In one embodiment of the present application, the silicon source gas may be, but is not limited to, one or more of monosilane (SiH4), disilane (Si2H6), chlorotrihydrogen silicon (SiH3Cl), dichlorodihydrogen silicon (SiH2Cl) and trichloromonohydrogen silicon (SiHCl3). In one embodiment of the present application, the silicon source gas may be monosilane. In another embodiment of the present application, the silicon source gas may be disilane.

[0053] In one embodiment of the present application, a carrier gas is also included, and the carrier gas can promote the flow of the silicon source gas, so that the silicon source gas enters the porous carbon and promotes the deposition of silicon. Specifically, the carrier gas can be, but is not limited to, one or more of argon, nitrogen and hydrogen. In one embodiment of the present application, the carrier gas can be argon. In another embodiment of the present application, the carrier gas can be nitrogen.

[0054] In one embodiment of the present application, the reaction temperature is less than or equal to 800°C, the reaction time is 1h-100h, and the reaction pressure is negative 5kPa-30kPa. Suitable reaction conditions can form a silicon-carbon core with high energy density. Specifically, the reaction temperature may be, but is not limited to, less than or equal to 800°C, less than or equal to 700°C, less than or equal to 600°C, less than or equal to 500°C, less than or equal to 400°C, or less than or equal to 300°C, etc.; the reaction time may be, but is not limited to, 1h, 20h, 40h, 60h, 80h, or 100h, etc.; the reaction pressure may be, but is not limited to, negative 5kPa, 8kPa, 10kPa, 15kPa, 18kPa, 20kPa, or 30kPa, etc. In one embodiment of the present application, the reaction temperature may be 500°C-800°C, and the reaction pressure may be negative 5kPa-20kPa.

[0055] The present application provides a negative electrode sheet, which includes the negative electrode material described in any one of the above embodiments as a negative electrode active material, thereby improving the conductivity and rate performance of the negative electrode sheet. Figure 1 , is a schematic diagram of the cross-sectional structure of a negative electrode sheet provided in one embodiment of the present application. The negative electrode sheet 100 includes a negative electrode current collector 10 and a negative electrode active material layer 11 disposed on the surface of the negative electrode current collector 10, and the negative electrode active material layer 11 includes the negative electrode material described in any of the above embodiments. The negative electrode sheet provided in the present application has good rate performance and high cycle stability.

[0056] In one embodiment of the present application, the negative electrode current collector may include, but is not limited to, at least one of copper, titanium, nickel and stainless steel. In one embodiment of the present application, the negative electrode current collector may be copper foil.

[0057] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode conductive agent, which can increase the conductivity of the negative electrode material and improve the electronic conductivity. Specifically, the negative electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the negative electrode conductive agent may be graphite. In another embodiment of the present application, the negative electrode conductive agent may be carbon black.

[0058] In one embodiment of the present application, the negative electrode active material layer also includes a negative electrode binder, which can improve the binding ability of the components in the negative electrode active material layer and improve the binding ability between the negative electrode active material layer and the current collector. Specifically, the negative electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the negative electrode binder can be polyvinylidene fluoride. In another embodiment of the present application, the negative electrode binder can be sodium carboxymethyl cellulose.

[0059] The present application also provides a battery, comprising a positive electrode sheet and a negative electrode sheet provided by any one of the above embodiments. The negative electrode sheet has a long cycle life and good fast charging performance, so the battery provided by the present application has excellent charging and discharging performance, good low temperature performance, and long service life.

[0060] In one embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0061] In one embodiment of the present application, the positive electrode current collector may be, but is not limited to, at least one of copper, aluminum, nickel and stainless steel. In one embodiment of the present application, the positive electrode current collector may be aluminum foil.

[0062] In one embodiment of the present application, the positive electrode active material can improve the conductivity, capacity and cycle stability of the positive electrode plate. The specific positive electrode active material can include but is not limited to at least one of lithium iron phosphate material, lithium iron manganese phosphate, lithium cobalt oxide material, lithium manganese oxide material, nickel cobalt manganese material and nickel cobalt aluminum material. In one embodiment of the present application, the positive electrode active material can be a lithium cobalt oxide material.

[0063] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode conductive agent. The positive electrode conductive agent can increase the conductivity between the active materials and improve the electronic conductivity. Specifically, the positive electrode conductive agent may include but is not limited to at least one of graphite, carbon black, acetylene black and graphene. In one embodiment of the present application, the positive electrode conductive agent may be graphite. In another embodiment of the present application, the positive electrode conductive agent may be carbon black.

[0064] In one embodiment of the present application, the positive electrode active material layer also includes a positive electrode binder, which can improve the binding ability of the components in the positive electrode active material layer and improve the binding ability between the positive electrode active material layer and the positive electrode current collector. Specifically, the positive electrode binder can be, but is not limited to, one or more of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, polystyrene, polybutadiene, acrylic resin, epoxy resin, polyethylene oxide, sodium carboxymethyl cellulose and styrene-butadiene latex. In one embodiment of the present application, the positive electrode binder can be polyvinylidene fluoride.

[0065] In one embodiment of the present application, the battery further includes a separator disposed between the positive electrode sheet and the negative electrode sheet. Specifically, the separator may be, but is not limited to, a woven membrane, a non-woven fabric, a microporous membrane, a composite membrane, a rolled membrane, or a separator paper. In one embodiment of the present application, the battery further includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and may be, but is not limited to, a substance that can be used as a battery electrolyte in the art.

[0066] The present application also provides an electric device, which includes a battery provided by any of the above embodiments. The electric device provided by the present application has excellent comprehensive performance and strong market competitiveness. The electric device of the present application may refer to a vehicle, an electronic device, an energy storage system, etc. In one embodiment of the present application, the battery can be used in a vehicle to increase the life cycle of the vehicle's electricity consumption. In another embodiment of the present application, the battery can also be used in an electronic device to increase the cycle stability of the battery of the electronic device and improve the battery capacity.

[0067] The effect of the technical solution of the present application is further illustrated below through specific examples.

[0068] Example 1

[0069] Take 4g of binder (polyacrylonitrile) and dissolve it in 150g of N-methylpyrrolidone, add 110g of N-methylpyrrolidone containing 4% of conductive agent (carbon nanotubes) by mass, stir well, add 800g of particle size D50 of 7μm-10μm and specific surface area of ​​50m 2 / g of silicon-carbon core was placed in a kneading furnace under a nitrogen atmosphere and mixed for 2 h at a speed of 20 r min -1 , obtaining a mixture;

[0070] Transfer the mixture from the kneading pot to the CVD rotary furnace and introduce N2 for more than 1 hour to fully exhaust the O2 in the furnace. Adjust the furnace speed to 10 r min -1 , keep N2 flowing, raise the temperature to 550°C, and heat treat for 2h to obtain a negative electrode material precursor;

[0071] Stop N2 flow and increase the temperature to 1 L min -1 The carbon source gas (acetylene) was introduced at a flow rate of 1.50°C to carry out the reaction. The reaction time was 30 min and the reaction temperature was 550°C. The introduction of acetylene was stopped, N2 was introduced again and heating was stopped to restore the furnace temperature to room temperature to obtain the negative electrode material.

[0072] Example 2

[0073] The difference from Example 1 is that the binder is 8 g of glucose, and kneading is carried out at 150° C. under N 2 protection without using a solvent.

[0074] Example 3

[0075] The difference from Example 1 is that the binder is 2 g of polyacrylonitrile.

[0076] Example 4

[0077] The difference from Example 1 is that the conductive agent is 2 g of carbon nanotubes.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that no conductive agent is added.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that no carbon source gas is introduced and the binder is 4 g of polyacrylonitrile.

[0082] Performance Testing

[0083] The negative electrode materials prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 were tested for specific surface area, and the test results are shown in Table 1.

[0084] The negative electrode materials prepared in the above Examples 1-4 and Comparative Examples 1-2 were subjected to a powder resistivity test, and the test process was carried out in accordance with GB / T24533-2019. The test results are shown in Table 1.

[0085] The negative electrode materials prepared in the above Examples 1-4 and Comparative Examples 1-2 were subjected to a particle size test, and the test process was carried out in accordance with GB / T24533-2019. The test results are shown in Table 1.

[0086] The negative electrode materials prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2, the conductive additive carbon black, and the adhesive (sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 1:1) were weighed in a mass ratio of 94:2:4, and the slurry was prepared with a beater to obtain the negative electrode slurry; then the above-mentioned negative electrode slurries were coated on the surface of the negative electrode current collector (specifically copper foil), and then dried and cut into pieces in turn, and assembled into a button-type half-cell with a lithium metal sheet in a glove box. At a constant temperature of 25±2°C, a constant current charge and discharge mode test was performed using a charge and discharge instrument, the discharge cut-off voltage was 0.005V, and the charge cut-off voltage was 2V. The first week of charge and discharge test was performed at a current density of 1C / 10 to obtain the reversible capacity and the first coulomb efficiency. First coulomb efficiency = first charge capacity / first discharge capacity×100%.

[0087] Preparation of a full battery: The negative electrode materials prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 are configured with graphite to form a composite with a specific capacity of 450 mAg / h, and then mixed with a conductive additive and a binder at a mass ratio of 94:2:4 to prepare a negative electrode slurry, and the negative electrode slurry is coated on a current collector (specifically a copper foil) to obtain a negative electrode sheet; the positive electrode active material ternary NMC532, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a weight ratio of 96.7:1.7:1.6, and then coated on an Al foil, dried, and cold pressed to obtain a positive electrode sheet; a polypropylene porous polymer film is used as an isolation film; the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet are stacked in order, so that the isolation film is between the positive electrode sheet and the negative electrode sheet to play an isolation role, and then wound to obtain a bare battery cell. The bare cell is placed in the outer packaging, injected with the prepared electrolyte and packaged, and the full cell is obtained through the process of formation, degassing, trimming, etc. The electrolyte is a common silicon negative electrode electrolyte formula on the market.

[0088] The full batteries prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 were subjected to constant current charge and discharge tests at 25°C using a charge and discharge instrument, with a discharge cut-off voltage of 2.75V and a charge cut-off voltage of 4.2V. The charge and discharge tests were all conducted at a current density of 1C. The capacity retention rate of the battery after 300 cycles was recorded, and the capacity retention rate = the discharge capacity of the 300th cycle / the discharge capacity of the 1st cycle × 100%. The test results are shown in Table 2.

[0089] The half-cells prepared in the above-mentioned Examples 1-4 and Comparative Examples 1-2 were subjected to rate performance tests. Rate performance tests: At 25°C, a charge-discharge instrument was used to perform constant current charge-discharge tests on the above-mentioned full cells, with a discharge cut-off voltage of 1mV and a charge cut-off voltage of 1.5V. The charge-discharge tests were performed at current densities of 0.1C, 0.5C, 1C, 3C, and 5C, respectively. The corresponding rate performance = discharge capacity at the corresponding current density / discharge capacity at the current density of 0.1C × 100%; the test results are shown in Table 2.

[0090] Table 1 Negative electrode material performance test

[0091]

[0092] Table 2 Battery performance test results

[0093]

[0094] It can be seen from Examples 1-4 and Comparative Examples 1-2 that the negative electrode material provided by the present application includes a silicon-carbon core and a composite coating layer arranged on the surface of the silicon-carbon core, the composite coating layer includes a conductive network and amorphous carbon filled in the gaps of the conductive network, and the negative electrode material has good structural stability, high electrical conductivity, and high energy density, which improves the rate performance and cycle stability of the battery and extends the service life of the battery. It can be seen from Example 1 and Examples 2-4 that the appropriate content of the binder and the conductive agent can reduce the specific surface area of ​​the negative electrode material, improve the rate performance, structural stability and energy density of the negative electrode material, and improve the electrochemical performance of the battery. It can be seen from Example 1 and Comparative Examples 1-2 that the conductive network in the negative electrode material provided by the present application can improve the conductivity and first-cycle efficiency of the negative electrode material, and the carbon layer can reduce the specific surface area of ​​the negative electrode material, improve the structural stability and cycle performance of the negative electrode material, and help improve the cycle life and electrochemical performance of the battery.

[0095] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material comprises a silicon-carbon core and a composite coating layer arranged on the surface of the silicon-carbon core, wherein the composite coating layer comprises a conductive network and amorphous carbon filled in the gaps of the conductive network.

2. The negative electrode material according to claim 1, characterized in that The silicon-carbon core comprises porous carbon and silicon nanoparticles filled in the pores of the porous carbon; The silicon nanoparticles include one or more of crystalline silicon and amorphous silicon.

3. The negative electrode material according to claim 1, characterized in that The conductive network is formed by a conductive agent; The conductive agent includes one or more of carbon nanotubes, conductive carbon black and nano silver wires.

4. The negative electrode material according to claim 1, characterized in that In the negative electrode material, the mass percentage of the composite coating layer is 0.01%-5%.

5. A method for preparing a negative electrode material, characterized in that: include: The conductive agent, the binder and the silicon-carbon core are mixed and heat treated to obtain a negative electrode material precursor; The negative electrode material precursor is mixed with a carbon source gas and vapor deposited to obtain the negative electrode material.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the silicon-carbon core, the binder and the conductive agent is 100:(0.1-1):(0.2-1).

7. The preparation method according to claim 5, characterized in that: The temperature of the heat treatment is 500° C.-550° C., and the time of the heat treatment is greater than or equal to 3 hours.

8. The preparation method according to claim 5, characterized in that: The temperature of the vapor deposition is less than or equal to 600° C., and the time of the vapor deposition is 30 min-2 h; The carbon source gas includes one or more of alkanes, alkenes, alkynes and aromatic hydrocarbons.

9. The preparation method according to claim 5, characterized in that: The binder includes one or more of acrylic acid, acrylic acid ester, terephthalic acid, polyacrylonitrile, glucose, maltose, polyacrylic acid, polymethyl methacrylate, phenolic resin and arabic resin.

10. A negative electrode plate, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, and the negative electrode active material layer comprises the negative electrode material according to any one of claims 1 to 4 or the negative electrode material prepared by the preparation method according to any one of claims 5 to 9.

11. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 10.

Citation Information

Cited By

  • Negative electrode material

    WO2026052154A1